Patron-Driven Acquisition: Current Practice of eBook Selection in Malaysian Academic Libraries - Abdullah, Che Zainab Hj; Kassim, Norliya Ahmad (Qualitative and Quantitative Methods in Libraries, 2017)
This paper reports the findings of a study on e-book selection practices and its relationship with library’s return on investment. In this preliminary study, questionnaires were distributed to selected professional librarians who are responsible either with e-book acquisition or handling e-book at reference desk in public and private academic  libraries in Klang Valley, Malaysia. The finding reveals  that the respondents have   positive  perceptions on the current practices of e-book selection (resource sharing and  accessibility) and  return on investment. The result also indicates a positive and moderate relationship between resource sharing and library’s return on investment.